Electronic Structure and Optical Properties of Gaas1-Xpx: A First-Principles Study - Al-Jobory, Alaa A.; Ahmed, Wael, I.; A., Ibrahim J. (Iraqi Journal of Science, 2020)
In this work, the effects of x-value on electrical and optical properties was studied for the two dimensional (2D)GaAs1-xPxstructure by applying the density functional theory.We found that the gallium arsenide(GaAs) and gallium phosphide(GaP) monolayers are bound to each other, while the charge transfer between these two materialsleads to tuning the band gap value between 1.5 eV for GaAs to 2.24 eV for GaP. The density of state, band structure, and optical properties are investigated in this paper.